Poverty alleviation resettlement in China reduces deforestation - Feifei Chen; Wei Chen; Huanguang Qiu (Proceedings of the National Academy of Sciences, 2025)
Deforestation frequently accompanies poverty, yet various antipoverty programs in many countries have exhibited mixed results in addressing deforestation. Poverty Alleviation Resettlement (PAR) stands out as one of the few government-led resettlement programs designed to alleviate poverty, offering comprehensive follow-up support for quality of life and employment after relocation. Our study uncovered empirical evidence of the PAR program’s impact on forest quality. Through a multiperiod difference-in-differences analysis of remote sensing and household survey data, we found that the PAR program significantly curbed deforestation in the participating counties and reduced forest-clearing activities among the resettled households, even those relocating to rural villages. Mechanism analysis revealed that the program discouraged deforestation by enhancing market accessibility, fostering nonfarm employment opportunities, and elevating income levels. The study underscores that altering livelihood strategies and lifestyles is essential for resettlement programs to effectively mitigate ecological degradation.